New high-pressure tetragonal polymorphs of SrTiO3—molecular orbital and Raman band change under pressure. (7th June 2018) - Yamanaka, Takamitsu; Ahart, Muhtar; Mao, Ho-kwang; Yan, Hao
Abstract: The vibrational and structural properties of SrTiO3 were investigated using Raman spectroscopy, synchrotron x-ray powder diffraction up to 55 GPa at 300 K, and ab initio quantum chemical molecular orbital (MO) calculations. These measurements and calculations revealed the structure transformation from cubic to tetragonal phase at about 9 GPa. Above 9 GPa, sharper new peaks were associated with a tetragonal structure. At about 30 GPa some bands disappeared and several new bands emerged. Structure transformation from I 4/ mcm to a new structure of P 4/ mbm was found at above 30 GPa by Rietveld profile fitting analysis. The diffraction pattern gave no indication of a Cmcm orthorhombic phase. Ab initio MO calculation proved the change of the molecular orbital coupling with a structure transformation. The Mulliken charge of Ti is increased with increasing pressure in the cubic phase, but the Sr charge continuously decreased. The d – p – π hybridization of the Ti–O bond and localizing the electron density are decreased with increasing pressure. The Ti–O bond becomes shorted in the P 4/ mbm phase and the change in the Ti charge accelerated more. All present investigations by x-ray diffraction, Raman spectra study and MO calculation show consistent results.